Geoinformatics for landscape ecology and biodiversity research - Amarnath, Giriraj; Bajracharya, B.; Shrestha, B. (2012)
This review paper evaluates the potential of remote sensing for assessing landscape and species diversity in mountainous terrain. Understanding the complex mechanism of biodiversity necessitate its spatial and temporal dynamics and synergetic adoption of measurement approaches with long-term plot inventories. In view of this, importance of geoinformatics - which can be seen as a combination of integrating tools such as Geographic Information System (GIS), satellite remote sensing, Global Positioning System (GPS), and information and communication technologies, are realized as complimentary systems to ground-based studies. This paper addresses how wide range of geospatial tools can be used in monitoring and assessment of biodiversity. Further discussions are made on the wide variety of landscape ecological application tools, and the required data from broad spatial extents that cannot be collected through field-based methods. Remote sensing data and techniques address these needs, which include identifying and detailing the biophysical characteristics of species? habitats, predicting the distribution of species and spatial variability in species richness, and detecting natural and human-caused changes at scales ranging from individual landscapes to the entire world.